Circular waste management of electric vehicle batteries: Legal and technical perspectives from the EU and the UK post Brexit. (May 2021) - Malinauskaite, J.; Anguilano, L.; Rivera, X. Schmidt
Abstract: In light of the climate change, interdisciplinary solutions are needed to deal with end-of-life lithium-ion batteries (LIBs) that are used in Electric vehicles (EVs) in order to avoid a waste problem in the future. Building on both legal and technical perspectives, this paper criticises the current EU and UK frameworks and policies on batteries waste management which fail to address technological innovation, especially, in terms of the creation of a market for 'second life' of EV batteries which are subject to the electrochemical performance and durability and safety parameters, as well as LIB recycling in support of a circular economy. Most importantly, it also addresses recent developments in the EU in terms of a proposal for the EU new Batteries Regulation and the impact of Brexit in the UK for its future policy shape.